2014
DOI: 10.5301/jva.5000200
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Fibrin in Blood Thrombi Formed in Hemodialysis Central Venous Catheters: A Pilot Study on 43 CVCs

Abstract: The analytical method presented here proved to be a rapid and effective way for quantifying fibrin content in thrombi formed on CVCs with potential application in future clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…These results were also found by a study evaluating the thrombus present in central venous catheters by Two-photon laser scanning microscopy (2) . This type of microscopy reaches a greater tissue depth when compared to Confocal Laser Scanning Microscopy, and the greater the tissue depth evaluated, the greater the red blood cell and white blood cell concentration, and the smaller the amount of fibrin interconnected to the cells (2) . In another study, a venous thrombus was observed by Two Photon Laser Scanning Microscopy in which the fibrin plate was surrounded by white blood cells close to the inner wall of the catheter opening (3) .…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…These results were also found by a study evaluating the thrombus present in central venous catheters by Two-photon laser scanning microscopy (2) . This type of microscopy reaches a greater tissue depth when compared to Confocal Laser Scanning Microscopy, and the greater the tissue depth evaluated, the greater the red blood cell and white blood cell concentration, and the smaller the amount of fibrin interconnected to the cells (2) . In another study, a venous thrombus was observed by Two Photon Laser Scanning Microscopy in which the fibrin plate was surrounded by white blood cells close to the inner wall of the catheter opening (3) .…”
Section: Discussionsupporting
confidence: 71%
“…Initial forming and maturing of the different thrombotic tissue components may lead to occlusion of the CVC lateral openings, mainly due to different conformations of the fibrin inside the opening and its adsorption to polymeric materials. Fibrin deposition on the catheter causes the surface to encapsulate, forming a sheath at the distal tip of the catheter (4)(5) .The process of protein adsorption to the polymer may become irreversible, and tissue dissolution becomes ineffective even by introducing fibrinolytic agents due to strong covalent bonds between plasma proteins and the catheter wall (2)(3) . The activation of a coagulation cascade increases the tendency for thrombus formation, which is an important cause of complications in patients using a venous catheter, which can not only lead to thrombosis near the vascular access, but also to emboli formation, deep venous thrombosis and the possible development of cardiac ischemia (8)(9)(10)(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations